Hamstring muscle kinematics during the acceleration phase of sprinting - Higashihara, A.; Nagano, Y.; Takahashi, K.; Fukubayashi, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recent video analysis of hamstring strains showed that many injuries involve trunk flexion while running at high speed, an action usually seen during acceleration (Orchard, 2002; Verrall et al., 2005). Based on this observation, trunk flexion during sprinting is therefore a risk for hamstring strain injury. However, thus far this hypothesis has not been scientifically validated. The purpose of this study was to investigate hamstring muscle kinematics during the acceleration phase of sprinting, and compare it with the maximum speed phase. Methods Eight male track and field athletes (age, 18.6 ± 7.9 years) performed maximal sprint from 2 starting lines, set approximately 15 and 60 m from the center of the measurement area. A three-dimensional musculoskeletal model was used to compute muscle lengths and muscle-tendon forces of the biceps femoris (BF), semitendinosus (ST), and semimembranosus (SM) muscles during the sprinting gait cycle. Hip flexion, knee flexion, and pelvic anterior tilt angles were also calculated. Results Hip and knee flexion angles at foot strike were significantly greater during the acceleration phase than during the maximum speed phase (p < 0.001). A similar trend was observed for the pelvic anterior tilt angle (foot strike, p < 0.01; maximum, p < 0.001). Hamstring muscle lengths peaked during the terminal swing of the gait cycle, and at foot strike, they were significantly greater during the acceleration phase than during the maximum speed phase (BF, p < 0.01; ST and SM, p < 0.001). The hamstring muscle-tendon forces showed no significant difference between the 2 phases. Peak muscle-tendon forces of the BF muscle and the ST and SM muscles occurred during the terminal swing and initial stage of the gait cycle, respectively. Discussion The results of this study showed that compared to the maximum speed phase of sprinting, sprinters tend to have more forward trunk lean during the acceleration phase, and this may cause stretching of the hamstring muscles at foot strike. The results also showed that peak muscle-tendon forces of the BF muscle occurred during the terminal swing of the gait cycle, simultaneous with the maximal stretching of the BF muscle. The BF muscle, the most commonly injured among the hamstring muscles (Woods et al., 2004), is subjected to excessive loads during the terminal swing of the gait cycle when it is in its most elongated position.